Oral Kaposi Sarcoma in HIV-seronegative Saudi patient: Literature review and case report - Asmaa Faden; Manal AlSheddi; Mohammed AlKindi; Lama Alabdulaaly (Elsevier, 2017)
Kaposi Sarcoma (KS) is an intermediate neoplasm affecting the endothelial cells of mucous membranes and skin. It arises most commonly among HIV-infected individuals. We present an intra-oral KS in an 80-year-old Saudi male patient, who is HIV-seronegative, non-immunosuppressed, and with no history of organ transplantation. The patient was treated with fractionated radiation therapy, and had no recurrence in the 48 months of follow-up. The clinical disease, histologic features, and treatment modality used, as well as the relative literature are presented in this paper. Keywords: Kaposi sarcoma, HIV-seronegative, Non-immunosuppressed, Pyogenic granuloma